From Tradition to Transformation: Alumni Networks, Digital Leadership, and Entrepreneurial Innovation in Strengthening Pesantren Sustainability - Muhammad Idris; Akhmad Fauzi Hamzah (Organon: Journal of Islamic Education Management, 2026)
This study examines the transformation of pesantren in responding to social change and the challenges of the digital era. Using a qualitative approach with a case study design, data were collected through in-depth interviews, observations, and documentation involving institutional leaders and relevant stakeholders. The findings reveal that pesantren transformation extends beyond technological adaptation and involves broader institutional changes in educational orientation, leadership practices, entrepreneurial development, and social networking. Pesantren have increasingly adopted adaptive strategies through digital competency development, entrepreneurship programs, and institutional innovation while maintaining their religious values and identity. Leadership plays a crucial role in directing institutional change, particularly through adaptive and value-based approaches that support organizational development. Furthermore, alumni networks contribute significantly to institutional sustainability by strengthening social support and institutional legitimacy. Despite facing challenges such as technological disparities, infrastructure limitations, and human resource readiness, pesantren demonstrate considerable potential to remain relevant and sustainable in contemporary society. This study highlights that the transformation of pesantren is not merely a process of modernization but represents a strategic effort to balance religious traditions with evolving societal demands.